A STUDY OF THE DEFENSIVE BEHAVIORS OF FREE-RANGING DEKAY’S BROWNSNAKES, STORERIA DEKAYI (HOLBROOK, 1836) - Gray, Brian S. (Journal of North American Herpetology, 2015)
The defensive behaviors of free-ranging Dekay’s Brownsnakes, Storeria dekayi, were studied at a site in Erie County, Pennsylvania, USA. Twenty-nine unique sequences of defensive behavior were documented. A total of 50 individual snakes (26 males and 24 females) provided 88 observations during the initial phase, of which 78% (n = 69) were of snakes that remained in place. Snakes were tapped with the investigator’s hand to elicit defensive behaviors during the contact phase. Snakes were more than twice as likely to attempt to flee during the contact phase (46%) than during the initial phase (22%). During the contact phase, mean surface body temperatures were significantly higher in snakes attempting to flee (22.3 ± 1.3 °C) than those that remained in place (16.1 ± 2.2 °C). The most frequently observed response during the contact phase was dorso-ventral flattening of the head and body (n = 42). During capture, most snakes (94%) smeared their cloacal contents on themselves and the investigator’s hand.